2016
DOI: 10.1016/j.immuni.2016.04.010
|View full text |Cite
|
Sign up to set email alerts
|

The DNA Structure-Specific Endonuclease MUS81 Mediates DNA Sensor STING-Dependent Host Rejection of Prostate Cancer Cells

Abstract: Self-DNA is present in the cytosol of many cancer cells and can promote effective immune rejection of tumor cells, but the mechanisms leading to the presence of cytosolic DNA are unknown. Here, we report that the cleavage of genomic DNA by DNA structure-specific endonuclease MUS81 and PARP-dependent DNA repair pathways leads to the accumulation of cytosolic DNA in prostate cancer cells. The number of nuclear MUS81 foci and the amount of cytosolic dsDNA increased in tandem from hyperplasia to clinical stage II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
119
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(135 citation statements)
references
References 47 publications
(55 reference statements)
5
119
0
2
Order By: Relevance
“…In pilot experiments, we observed that the treatment of mammalian cells with X-irradiation led to an accumulation of ssDNA in the cytosol, an observation consistent with several other studies that report that genomic stress is associated with the accumulation of ssDNA in the cytosol (Shen et al 2015;Ho et al 2016). To further investigate whether DNA damage processing can lead to DNA fragments escaping the nucleus, a range of breast cancer cell lines (MCF7, BT474, MDA-MB-231, HCC1806, and T47D) was treated with IR (X rays) or DNA-damaging chemotherapeutics (mitomycin C or cisplatin) that induce distinct forms of DNA damage.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In pilot experiments, we observed that the treatment of mammalian cells with X-irradiation led to an accumulation of ssDNA in the cytosol, an observation consistent with several other studies that report that genomic stress is associated with the accumulation of ssDNA in the cytosol (Shen et al 2015;Ho et al 2016). To further investigate whether DNA damage processing can lead to DNA fragments escaping the nucleus, a range of breast cancer cell lines (MCF7, BT474, MDA-MB-231, HCC1806, and T47D) was treated with IR (X rays) or DNA-damaging chemotherapeutics (mitomycin C or cisplatin) that induce distinct forms of DNA damage.…”
Section: Resultssupporting
confidence: 89%
“…Similarly, treatment of mouse B-cell lymphoma cells and human lung carcinoma cells with a replication inhibitor showed induction of cytosolic DNA (Shen et al 2015). Further findings suggest the possibility that release of MUS81-induced cytosolic DNA by prostate cancer cells contributes to STING activation (Ho et al 2016), where such fragments might be a by-product of MUS81-mediated replication fork processing in these cells (Ciccia et al 2008). Moreover, RNase H2 deficiency, the most frequent cause of the autoinflammatory disease Aicardi-Goutières syndrome (AGS), triggers cGAS/STING activation (Crow and Manel 2015;Mackenzie et al 2016;Pokatayev et al 2016).…”
Section: Discussionmentioning
confidence: 73%
“…Although extrinsic sensing of tumor cell debris is confined to cells with phagocytic capability, it appears that ubiquitous cell-intrinsic mechanisms exist for sensing genotoxic stress and DNA damage, which has long been appreciated as a robust inducer of the IFN-I response [54,55]. As part of a cell-intrinsic replicative stress response, prostate cancer cells continuously shed genomic DNA into the cytosol due to cleavage of DNA at stalled replication forks by the DNA repair endonuclease MUS81, which results in activation of STING-dependent cytosolic DNA sensing and contributes to tumor immunogenicity and rejection [56]. Extra-chromosomal telomere repeat DNA (ECTR) fragments, generated by trimming of telomeres elongated through the pro-oncogenic alternative lengthening of telomeres (ATL) pathway, accumulate in ~10–15% of cancer cells and can also trigger cGAS–STING–IFN-I signaling [57].…”
Section: Cancer Cancer Therapy and Genotoxic Stressmentioning
confidence: 99%
“…Recently, the suppressive role of TMEM173 in tumorigenesis was suggested in several cancer types, such as prostate cancer, colorectal carcinoma and melanomas [1012]. However, its function in HCC remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%